2018
DOI: 10.20517/2394-5079.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different biomarkers for the management of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and the second cause of cancer related death due to latent liver disease, late diagnosis and non-available therapeutic treatment. Liver biopsy is still the gold standard in order to know the molecular biology of the tumor, its behaviour and invasive characteristics. Conventional diagnosis methods for HCC detection include imaging and serological tests with low sensitivity and specificity. In this review, we focus on the potential utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 114 publications
2
8
0
Order By: Relevance
“…These results go along with Rojas et al (5) who demonstrated that AFP and GPC3 combination carried higher sensitivity and specificity (98.5% and 97.8%, respectively). Moreover, GPC3 was detected in around one third of confirmed HCC patients with normal serum AFP.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results go along with Rojas et al (5) who demonstrated that AFP and GPC3 combination carried higher sensitivity and specificity (98.5% and 97.8%, respectively). Moreover, GPC3 was detected in around one third of confirmed HCC patients with normal serum AFP.…”
Section: Discussionsupporting
confidence: 84%
“…Glypican-3 (GPC3) is one of the glypican family of glycosyl-phosphatidylinositol-anchored cell-surface heparan-sulfate proteoglycans. The levels of which are significantly elevated in HCC patients (5) . Trials showed that serum GPC3 is an early sensitive and specific biomarker for initial laboratory diagnosis of HCC and for detection of recurrence (12) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…47.73%. These values were in line with previous studies conducted on AFP's sensitivity which are usually in the range of 41% to 84%(10,(28)(29)(30) which is a very broad range due to different Aqsa Ahmed et al,…”
supporting
confidence: 92%
“…the MedCalc diagnostic test evaluation calculator, different metrics linked to a biomarker's diagnostic capacity were computed after the number of True positives, True negatives, False positives, and False negatives were determined. The specificity was found to be 95.45 percent, while the sensitivity was 77.27 percent which are excellent values for a biomarker of HCC, and these values are far better than reported for AFP(29,30). The test's accuracy was determined to be 86.36 percent which further enhances confidence in the diagnostic ability of this candidate biomarker.…”
mentioning
confidence: 73%